Activity-dependent Synaptic Recruitment of Neuroligin 1 in Spinal Dorsal Horn Contributed to Inflammatory Pain. (15th September 2018) - Zhao, Ji-Yuan; Duan, Xing-Lian; Yang, Li; Liu, Jiang-Ping; He, Yong-Tao; Guo, Zhen; Hu, Xiao-Dong; Suo, Zhan-Wei
Highlights: Peripheral inflammation increased synaptic expression of NLGN1 in spinal dorsal horn. Synaptic activity regulates the abundance of NLGN1 at excitatory synapses. NLGN1-targeting siRNA inhibits synaptic accumulation of NMDA receptor. NLGN1-targeting siRNA alleviates inflammatory pain. Abstract: Neuroligin 1 (NLGN1), a cell adhesion molecule present at excitatory glutamatergic synapses, has been shown to be critical for synaptic specialization and N-methyl-d -aspartate (NMDA)-subtype glutamate receptor-dependent synaptic plasticity. Whether and how NLGN1 is engaged in nociceptive behavioral sensitization remains largely unknown. In this study, we found an activity-dependent regulation of NLGN1 synaptic expression in pain-related spinal cord dorsal horns of mice. The enhancement of neuronal activity by pharmacological activation of NMDA receptor (NMDAR) or removal of GABAergic inhibition in intact mice significantly increased NLGN1 concentration at synaptosomal membrane fraction. Intraplantar injection of complete Freund's adjuvant (CFA) also increased the NLGN1 expression at synapses. NMDAR might act through Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) and Src-family protein tyrosine kinase member Fyn to induce the synaptic redistribution of NLGN1. We also found that one of the important roles of NLGN1 was to facilitate the clustering of NMDAR at synapses. The NLGN1-targeting siRNA suppressed the synaptic expression of GluN2B-containing NMDAR in CFA-injected mice and meanwhile, attenuated the inflammatory mechanical allodynia and thermal hypersensitivity. These data suggested that tissue injury-induced synaptic redistribution of NLGN1 was involved in the development of pain hypersensitivity through facilitating the synaptic incorporation of NMDARs.